(untitled) (Jurnal Teknologi (Sciences & Engineering), 2017)
Absorbance spectra and energy band gap of synthesizing polyene from dechlorination of polyvinyl chloride (PVC) with varying synthesizing reaction times and doping percentages were examined in this paper. The reaction time of dechlorination was varied from 30 minutes, 1 hour, 2 hours and 4 hours. Polyene obtained from the dechlorination reaction was doped with potassium iodide (KI). Sample for UV/Vis test was prepared in the form of film. Modified EO film as control sample showed that there is only a single absorption peak around 327nm. The C-Cl adsorption band link from source link polymer was observed at 422nm and all polyene film samples and new bands absorption were observed from 422nm to 590nm, and 683nm upon the increase in reaction time. The lower energy band gap was observed at 683.18nm absorption with 1.08eV.